1978
DOI: 10.1017/s0376892900005889
|View full text |Cite
|
Sign up to set email alerts
|

Damage and Recovery of Tundra Vegetation

Abstract: This paper makes a series of broad recommendations concerning the understanding of damage and recovery of tundra vegetation. It deals primarily with arctic vegetation and with principles rather than specific recommendations or instructions for restoration. Actual procedures for restoration or revegetation, although practised, are still in their experimental stages.Despite this lack of established methods in tundra vegetation restoration, much can be done to help offset some of the worst effects of the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Horse trails were narrower than hiking trails probably because they are quite recently established and because of the habit of horse riding groups to travel in a single line. The impacts of skiing on trails seem to be mostly aesthetic as indicated in other studies (Bliss and Wein, 1972;Hernandez, 1973;Webber and Ives, 1978). Depending on the study, snow depth between 1 and 25 cm has been found to be sufficient to reduce trampling impacts (Hammitt and Cole, 1998;Felix et al, 1992).…”
Section: Discussionmentioning
confidence: 83%
“…Horse trails were narrower than hiking trails probably because they are quite recently established and because of the habit of horse riding groups to travel in a single line. The impacts of skiing on trails seem to be mostly aesthetic as indicated in other studies (Bliss and Wein, 1972;Hernandez, 1973;Webber and Ives, 1978). Depending on the study, snow depth between 1 and 25 cm has been found to be sufficient to reduce trampling impacts (Hammitt and Cole, 1998;Felix et al, 1992).…”
Section: Discussionmentioning
confidence: 83%
“…Alternatively, it is possible that the disturbance associated with seismic exploration overcame the inherent inertia in these arctic plant communities (Starfield & Chapin 1996) and initiated succession towards new community types, which are more reflective of the present climate (e.g., Landhäusser & Wein 1993). This scenario is based on the idea that reference tundra plant communities are products of past climates, and thus may not be expected to return to the same condition following perturbation (Webber & Ives 1978). This hypothesis is supported by remarkably similar patterns of vegetation change (i.e., increased dominance by deciduous shrubs) in: (1) tundra plant communities subject to experimental warming (e.g., Chapin et al 1995; Bret‐Harte et al 2001; Walker et al 2006); (2) long‐term (40+ years) surveys of “undisturbed” tundra (Sturm et al 2001); and (3) other long‐term post‐disturbance studies (Racine et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In permafrost disturbance nutrient regime (Chapin and Shaver 1981). When surface disruption is severe enough, the effects are irreversible (Webber and Ives 1978;Lawson 1986). If low impact compression occurs and vegetation is left more or less intact, vehicle passage often produces "greenbelts" by compressing standing dead vegetation (Rickard and Brown 1974;Abele et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Winter-trail impacts have been thought to be largely aesthetic with no long-term effects (Bliss and Wein 1972;Hernandez 1973;Webber and Ives 1978). Although numerous studies published on winter trails reported initial (1-to 2-year) impacts, few data are available on the longer term effects of trails.…”
Section: Introductionmentioning
confidence: 99%